Eight‐month postprogram completion: Change in risk factors for chronic disease amongst participants in a 4‐month pedometer‐based workplace health program. (29th May 2013) - Freak‐Poli, Rosanne; Wolfe, Rory; Brand, Margaret; de, Maximilian; Peeters, Anna
<x xml:space="preserve">Abstract</x> Objective To evaluate whether participation in a 4‐month, pedometer‐based, physical activity, workplace health program is associated with long‐term sustained improvements in risk factors for type 2 diabetes and cardiovascular disease, 8 months after the completion of the program. Design and Methods A sample size of 720 was required. 762 Australian adults employed in primarily sedentary occupations and voluntarily enrolled in a workplace program were recruited. Demographic, behavioral, anthropometric and biomedical measurements were completed at baseline, 4 and 12 months. Results About 76% of participants returned at 12 months. Sustained improvements at 12 months were observed for self‐reported vegetable intake, self‐reported sitting time and independently measured blood pressure. Modest improvements from baseline in self‐reported physical activity and independently measured waist circumference at 12 months indicated that the significant improvements observed immediately after the health program could not be sustained. Approximately half of those not meeting guidelines for physical activity, waist circumference and blood pressure at baseline, were meeting guidelines at 12 months. Conclusions Participation in this 4‐month, pedometer‐based, physical activity, workplace health program was associated with sustained improvements in chronic disease risk factors at 12 months. These results indicate that such programs can have a long‐term benefit and thus a potential role to play in population prevention of chronic disease.